Filosofia analítica e a produção artística contemporânea: a teoria do conceito agregativo como proposta de superação do desafio da escalabilidade à teoria estética - Siqueira, Jean Rodrigues (2017)
The present work proposes an interdisciplinary investigation concerning the logic of the concept ART, that is, about the circumstances that justify the categorization of something through the predicative expression “is art”. Its fundamental historical premise is that in the final decades of the nineteenth century artistic production underwent structural changes whose radicalization in the following centuries unmistakably evidenced the limitations of aesthetic theories oriented by the classical model of definition. As the processes of categorization in the most diverse theoretical fields were understood in the light of this model until the midtwentieth century, it is possible to say that the aesthetic theory was confronted with the necessity of a new vision on the nature of these processes. Based on this premise, the guiding problem of this work was thought as an analog of the demands for scalability involving information systems: how to account for an exponential expansion and diversification of data without compromising the operational effectiveness of the support responsible for its processing? Hence the idea of a “scalability challenge” to the aesthetic theory and the problem of its overcoming, mainly in face of the unfolding of contemporary art. Taking the discussions produced in the context of contemporary philosophy as its bibliographic horizon, more specifically in the tradition known as “analytical philosophy”, this work defends the thesis that the cluster concept theory elaborated by the English philosopher Berys Gaut offers elements for an understanding of the logic of the concept ART capable of overcome the scalability challenge in a satisfactory way.